Selected Cytokines Serve as Potential Biomarkers for Predicting Liver Inflammation and Fibrosis in Chronic Hepatitis B Patients With Normal to Mildly Elevated Aminotransferases. Issue 45 (November 2015) - Deng, Yong-Qiong; Zhao, Hong; Ma, An-Lin; Zhou, Ji-Yuan; Xie, Shi-Bin; Zhang, Xu-Qing; Zhang, Da-Zhi; Xie, Qing; Zhang, Guo; Shang, Jia; Cheng, Jun; Zhao, Wei-Feng; et al.
Abstract : Abstract: Previous studies of small cohorts have implicated several circulating cytokines with progression of chronic hepatitis B (CHB). However, to date there have been no reliable biomarkers for assessing histological liver damage in CHB patients with normal or mildly elevated alanine aminotransferase (ALT). The aim of the present study was to investigate the association between circulating cytokines and histological liver damage in a large cohort. Also, this study was designed to assess the utility of circulating cytokines in diagnosing liver inflammation and fibrosis in CHB patients with ALT less than 2 times the upper limit of normal range (ULN). A total of 227 CHB patients were prospectively enrolled. All patients underwent liver biopsy and staging by Ishak system. Patients with at least moderate inflammation showed significantly higher levels of CXCL-11, CXCL-10, and interleukin (IL)-2 receptor (R) than patients with less than moderate inflammation ( P < 0.001). Patients with significant fibrosis had higher levels of IL-8 ( P = 0.027), transforming growth factor alpha (TGF-α) ( P = 0.011), IL-2R ( P = 0.002), and CXCL-11 ( P = 0.032) than the group without significant fibrosis. In addition, 31.8% and 29.1% of 151 patients with ALT < 2 × ULN had at least moderate inflammation and significant fibrosis, respectively. Multivariate analysis demonstrated that CXCL-11 was independently associated with at least moderate inflammation, and TGF-α and IL-2R independently correlated with significant fibrosis in patients with ALT < 2 × ULN. Based on certain cytokines and clinical parameters, an inflammation-index and fib-index were developed, which showed areas under the receiver operating characteristics curve (AUROC) of 0.75 (95% CI 0.66–0.84) for at least moderate inflammation and 0.82 (95% CI 0.75–0.90) for significant fibrosis, correspondingly. Compared to existing scores, fib-index was significantly superior to aspartate aminotransferase (AST) to platelet ratio index (APRI) and FIB-4 score for significant fibrosis. In conclusion, CXCL-11 was independently associated with at least moderate inflammation, whereas IL-2R and TGF-α were independent indicators of significant fibrosis in both, total CHB patients and patients with normal or mildly elevated ALT. An IL-2R and TGF-α based score (fib-index) was superior to APRI and FIB-4 for the diagnosis of significant fibrosis in patients with normal or mildly elevated ALT. Abstract : Supplemental Digital Content is available in the text